ACTIVE VENTILATION OF GRAIN IN STORAGE - Pavkov, Ivan; Radojčin, Milivoj (Journal on Processing and Energy in Agriculture, 2025)
Storing grain in silos cells and floor storage does not end its life cycle. Biochemical processes are active in the grain, most notably aerobic respiration and anaerobic respiration, which contribute to increased moisture and temperature in stored grain. Many factors contribute to the intensity of respiration; temperatures of the grain, type of grain, presence of damage or impurities, presence of grain pests, etc. In most cases, we are unable to resolve these issues without moving (elevating) the grain. However, there is one important factor that we can manage in the storage, the temperature of the stored grain and the relative air humidity in the intergranular space. When the temperature of stored grain is lowered the intensity of respiration is lowered as well. Depending on the quality of the equipment lowering the temperature in the grain mound can be accomplished in three ways:-          “elevation”,-          cooling the grain with cooled air (granifrigor device)-          cooling the grain with surrounding air – active ventilationCooling the grain with surrounding air (active ventilation) is a technically adequate and investment-acceptable method used by most silos, especially when compared to cooling the grain with cooled air (granifrigor device). With adequate and timely utilization of the active ventilation system, it is possible to achieve an effect that mimics that of a grainfrigor device, but with lower exploitation and investment costs.
Keywords: aktivna ventilacija; zrno; skaldištenje